2012
DOI: 10.3346/jkms.2012.27.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serologic Immunity to Diphtheria-Tetanus-Pertussis After Treatment of Korean Pediatric Hematology and Oncology Patients

Abstract: The aim of this study was to investigate the diphtheria-tetanus-pertussis antibody titers after antineoplastic treatment and to suggest an appropriate vaccination approach for pediatric hemato-oncologic patients. A total of 146 children with either malignancy in remission after cessation of therapy or bone marrow failure were recruited. All children had received routine immunization including diphtheria-tetanus-acellular pertussis vaccination before diagnosis of cancer. The serologic immunity to diphtheria, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…In fact, antibody titers to vaccine-preventable diseases decrease after anticancer treatment. 1,2 In addition, survivors are at increased risk of complications from vaccine-preventable diseases, such as those caused by human papillomaviruses (HPV) and influenza viruses. 2,3 …”
mentioning
confidence: 99%
“…In fact, antibody titers to vaccine-preventable diseases decrease after anticancer treatment. 1,2 In addition, survivors are at increased risk of complications from vaccine-preventable diseases, such as those caused by human papillomaviruses (HPV) and influenza viruses. 2,3 …”
mentioning
confidence: 99%
“…Median antibody level for diphtheria was higher in patients with acute lymphoblastic leukemia than in the control group (0.202 IU/ml vs 0.071, p<0.001) (16). In a study, only 56.8% of patients with hematologic disorders had completely protective levels of diphtheria antibody, that was lower than healthy children (88.3%) (17). Also, more than 50% patients after anti neoplastic therapy (18) and more than 83% dialysis patients (19) had lacked protective immunity for diphtheria.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies described that 56.8% of patients with hemato-oncologic illnesses (17), 17% of patients with acute lymphoblastic leukemia (20), 82% of pediatric patients with sarcoma after antineoplastic therapy (21) and 70% in Indian pre-school children (22) had completely protective immunity. Loss of immunity to previous vaccinations, necessity and timing of re-immunization remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Although Fioredda et al argued in 2005 that antibody defi ciency to vaccine-preventable diseases was not signifi cantly different in children after chemotherapy as compared to healthy controls, multiple other studies have shown the development of antibody defi ciency after commencement of chemotherapy with no resolution over time following the completion of therapy (van der Does-van den Berg et al 1981 ;Smith et al 1995 ;Feldman et al 1998 ;von der Hardt et al 2000 ;Nilsson et al 2002 ;Reinhardt et al 2003 ;Ek et al 2004 ;Zignol et al 2004 ;Brodtman et al 2005 ;Ek et al 2006 ;Cheng et al 2009 ;Zengin and Sarper 2009 ;Alavi et al 2010 ;Paulides et al 2011 ;Kwon et al 2012 ;Patel et al 2012 ;Van Tilburg et al 2012 ). A review of such studies was most recently conducted by Esposito et al ( 2010a ) and van Tilburg et al ( 2006 ).…”
Section: Introductionmentioning
confidence: 99%